You are on page 1of 6

Two Fourier transforms

Mark Reeder
February 6, 2012
1 Fourier transform of e
−(x/a)
2
The (complex) Fourier transform F[f] of a function f(x) is deﬁned by
1

_

−∞
f(x)e
−iωx
dx.
Our ﬁrst aim here is to derive the Fourier transform
F
_
e
−(x/a)
2
_
=
a

2
· e
−(aω/2)
2
, (1)
where a > 0 is a constant. Regard this transform as a function of ω:
F(ω) =
1

_

−∞
e
−(x/a)
2
· e
−iωx
dx,
and diﬀerentiate:
d

F(ω) =
1

·
1
−i
_

−∞
xe
−(x/a)
2
· e
−iωx
dx,
and now integrate by parts, with
u = e
−iωx
, dv = xe
−(x/a)
2
, du = −iωe
−iωx
, v = −(a
2
/2)e
−(x/a)
2
,
to get
d

F(ω) =
1

·
−a
2
2
·
_

−∞
e
−(x/a)
2
· e
−iωx
dx =
−a
2
2
· F(ω).
Solving this diﬀerential equation for F(ω) we get
F(ω) = F(0) · e
−(aω/2)
2
.
So it remains to determine F(0). This is essentially the Gaussian integral:
F(0) =
1

_

−∞
e
−(x/a)
2
dx,
which can be computed as follows. The trick is to compute the square of F(0) and use polar coordinates:
F(0)
2
=
_
1

_

−∞
e
−(x/a)
2
dx
_
2
=
1

_

−∞
_

−∞
e
−(x/a)
2
· e
−(y/a)
2
dx dy =
1

_

0
_

0
e
−(r/a)
2
r dr dθ =
1

· 2π·
a
2
2
=
a
2
2
,
so we get
F(0) =
a

2
,
hence
F(ω) =
a

2
· e
−(aω/2)
2
,
as claimed in (1).
If a =

2 then
F(ω) = F
_
e
−x
2
/2
_
= e
−ω
2
/2
,
so the function e
−x
2
/2
is its own Fourier transform.
In general, a smaller a gives a bigger spike in the graph of f(x) and a more spread-out graph of F(ω). And vice-versa. Here
are the superimposed graphs of f(x) = e
−(x/a)
2
(red) and F(ω) = e
−(aω/2)
2
(blue) for a = .5, 1.2,

2, 2.
Out[11]=
-4 -2 2 4
0.2
0.4
0.6
0.8
1.0
-4 -2 2 4
0.2
0.4
0.6
0.8
1.0
-4 -2 2 4
0.2
0.4
0.6
0.8
1.0
Out[15]=
-4 -2 2 4
0.2
0.4
0.6
0.8
1.0
2 Fourier sine transform of erfc x/a, where a > 0
The Fourier Sine transform F
s
[f] of a function f(x) is deﬁned by
F
s
[f] =
2
π
_

0
f(x) sin(ωx) dx.
We will use our previous calculations to derive the formula
F
s
[erfc(x/a)] =
2
π
·
1 −e
−(aω/2)
2
ω
, (2)
where a > 0 is a constant and erfc(x) is the complementary error function deﬁned by
erfc(x) =
2

π
_

x
e
−ξ
2
dξ,
with graph
Out[17]=
-2 -1 1 2
0.5
1.0
1.5
2.0
2
So we must compute the integral
F
s
[erfc(x/a)] =
2
π
_

0
erfc(x/a) sin(ωx) dx.
We write this as the the imaginary part of a complex integral:
F
s
[erfc(x/a)] =
2
π
· Im
_

0
erfc(x/a)e
iωx
dx. (3)
We now work on the complex integral. Switching the limits we compute:
_

0
erfc(x/a)e
iωx
dx =
2

π
_

0
_

x/a
e
−ξ
2
e
iωx
dξ dx
=
2

π
_

0
_

0
e
−ξ
2
e
iωx
dx dξ
=
2

π
_

0
e
−ξ
2
_

0
e
iωx
dx dξ
=
2

π
_

0
e
−ξ
2 1

_
e
iωaξ
−1
_

=
2

π
·
1

__

0
e
iωaξ−ξ
2
dξ −
_

0
e
−ξ
2

_
.
So we have
F
s
[erfc(x/a)] =
2
π
· Im
i
ω
[G(0) −G(ω)] , (4)
where G(ω) is the function deﬁned by
G(ω) =
2

π
_

0
e
iωaξ−ξ
2
dξ =
2
a

π
_

0
e
iωu−(u/a)
2
du and G(0) =
2

π
_

0
e
−ξ
2
dξ = 1. (5)
It follows that
F
s
[erfc(x/a)] =
2
π
·
1
ω
[1 −Re G(ω)] , (6)
and
Re G(ω) =
2
a

π
_

0
e
−(u/a)
2
cos(ωu) du. (7)
Thus, Re G(ω) is a multiple of the Fourier cosine transform of e
−(u/a)
2
.
We have already computed the complex Fourier transform
F
_
e
−(x/a)
2
_
=
a

2
· e
−(aω/2)
2
. (8)
And for any even function f(x) we have
_

−∞
f(x)e
−iωx
dx =
_

0
f(x)e
−iωx
dx +
_
0
−∞
f(x)e
−iωx
dx =
_

0
f(x)
_
e
−iωx
+ e
iωx
¸
dx = 2
_

0
f(x) cos(ωx) dx.
Taking f(x) = e
−(x/a)
2
, equation (8) gives
2
_

0
e
−(x/a)
2
cos(ωx) dx =

2π · F
_
e
−(x/a)
2
_
= a

π · e
−(aω/2)
2
.
Inserting this into (7) we get
Re G(ω) = e
−(aω/2)
2
,
3
and putting this into (6) we get
F
s
[erfc(x/a)] =
2
π
·
1 −e
−(aω/2)
2
ω
,
as claimed in (2).
3 The diﬀerential operator viewpoint
The calculation of F[e
−x
2
] in the ﬁrst section is illuminated by a more algebraic point of view. First, let us modify the
deﬁnition of F so that it takes functions of x to functions of the same variable x:
F[f(x)] =
1
2

π
_

−∞
f(y)e
−ixy
dy.
Now the derivative formula becomes
F[f

(x)] = ixf(x). (9)
On the other hand if we ﬁrst apply F and then diﬀerentiate, we get
d
dx
F[f] =
1
2

π
_

−∞
(−iy)f(y)e
−ixy
dy = −iF[xf],
so
F[f]

= −iF[xf] (10)
Consider the diﬀerential operator
D =
d
dx
+ x, D[f] = f

+ xf.
Using formulas (9) and (10), we have
F[D[f]] = F[f

+ xf] = ixF[f] + iF[f]

= iD[F[f]].
Thus F and D are linear operators such that
FD = iDF. (11)
If f is a solution of the diﬀerential equation D[f] = 0, then (11) implies that F[f] is also a solution. However, every solution
of D[f] = 0 is of the form
f(x) = Ce
−x
2
/2
,
where C = f(0) is a constant. Therefore there is a constant C such that
F[e
−x
2
/2
] = Ce
−x
2
/2
.
To ﬁnd C we evaluate at 0:
F[e
−x
2
/2
](0) =
1
2

π
_

−∞
e
−y
2
/2
dy =
1

π
_

−∞
e
−u
2
du = 1.
Thus, the equality
F[e
−x
2
/2
] = e
−x
2
/2
(12)
follows from commutation formula (11) and the Gaussian integral.
4
4 Eigenvectors of the Fourier Transform
In terms of linear algebra, equation (12) asserts that e
−x
2
/2
is an eigenvector of the operator F, with eigenvalue = 1, on
the complex vector space V of functions of the form p(x)e
−x
2
/2
, where p(x) is a polynomial. The vector space V is inﬁnite
dimensional, but note that V is a union of ﬁnite dimensional subspaces
V =

_
n=0
V
n
,
where V
n
= {p(x)e
−x
2
/2
: deg p(x) ≤ n} is a subspace of dimension
dimV
n
= n + 1.
Note that
D[p(x)e
−x
2
/2
] = p

(x)e
−x
2
/2
,
so V
n
= ker D
n+1
is the subspace of functions in V killed by D
n+1
.
The function
d
n
dx
n
e
−x
2
/2
belongs to V
n
and the Hermite polynomials H
n
(x) are deﬁned by
H
n
(x)e
−x
2
/2
= (−1)
n
d
n
dx
n
e
−x
2
/2
.
On the homework, you showed that
F[x
n
e
−x
2
/2
] = (−i)
n
H
n
(x)e
−x
2
/2
(13)
so F[V
n
] = V
n
for each n. Having found the eigenvector e
−x
2
/2
∈ V
0
, we now seek the remaining eigenvectors of F in V
n
.
Deﬁne another operator ι : V →V by ι[f](x) = f(−x). The Fourier inversion theorem is the equation
F
2
= ι.
It follows that F
4
= I and the eigenvalues of F on V are powers of i =

−1. More precisely, F has order two one the even
functions in V and order four on the odd functions in V . So the functions with F-eigenvalues ±1 are even and those with
F-eigenvalues ±i are odd.
In fact, H
n
= x
n
+ terms of lower degree, so equation (13) shows that if F has an eigenvector ψ which lies in V
n
but not in
V
n−1
, then the eigenvalue must be (−i)
n
. Hence for each n ≥ 0 there is a unique function ψ
n
(x) ∈ V
n
of the form
ψ
n
(x) = (x
n
+ lower terms)e
−x
2
/2
such that
F[ψ
n
] = (−i)
n
ψ
n
.
For example, we have
ψ
0
= e
−x
2
/2
, ψ
1
= xe
−x
2
/2
, ψ
2
= (x
2

1
2
)e
−x
2
/2
, ψ
3
= (x
3

3
2
x)e
−x
2
/2
, ψ
4
= (x
4
−3x
2
+
3
4
)e
−x
2
/2
.
To ﬁnd ψ
n
we consider a new diﬀerential operator
D
2
=
d
2
dx
2
−x
2
.
Using equations (9) and (10) we ﬁnd that D
2
commutes with F:
D
2
F = FD
2
.
5
It follows that F preserves each eigenspace of D
2
. That is, if D
2
[ψ] = λψ for some λ ∈ C then D
2
F[ψ] = λF[ψ]. We take
λ = −(2n + 1), and consider the equation D
2
ψ = −(2n + 1)ψ, or in other words,
ψ

+ (2n + 1 −x
2
)ψ = 0. (14)
This has a two dimensional solution space, but only one solution (up to scalar) lies in V . For ψ(x) = p(x)e
−x
2
/2
is a solution
of (14) in V exactly when
p

−2xp

+ 2np = 0. (15)
Writing p =

c
k
x
k
, equation (15) is equivalent to the recurrence formula
c
k+2
=
2(k −n)
(k + 2)(k + 1)
c
k
.
So (15) has a unique polynomial solution p
n
of degree n whose parity is that of n. Taking c
n
= 1, it is given by
p
n
(x) =
n/2

k=0
(−1)
k
_
n
2k
_
1 · 3 · · · (2k + 1)
2
k
x
n−2k
.
Since F preserves the one-dimensional space of solutions of (14) in V , we have
F[p
n
(x)e
−x
2
/2
] = λp
n
(x)e
−x
2
/2
for some constant λ. But then λ = (−i)
n
because it is an eigenvalue of F on a polynomial of degree n. Hence
ψ
n
(x) = p
n
(x)e
−x
2
/2
is the desired eigenfunction of F.
6